Deskripsi Perilaku Dan Faktor Penyebab Tantrum Pada Anak Di Kelompok B - Amuda, Merlin; Napu, Yakob; Tine, Nurhayati (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2024)
This study aims to describe the behavior and factors causing tantrums in group B children aged 5-6 years at Anggrek Kindergarten, Karya Baru Village, Dengilo District, Pohuwato Regency. The method used is descriptive qualitative, with the subjects of the study being five children who have tantrum behavior. Data collection techniques using observation interviews, and documentation then, then, data analysis techniques are carried out by triangulating thematic interview data, observation and documentation. The results of the study can be concluded that there are five children who experience tantrum behavior with behavior 1) easily angry 2) like to throw tantrums 3) like to hurt themselves. The identified causal factors are the obstruction of the child's desires, wrong parenting patterns from parents, the child's stress, discomfort with the surrounding conditions, wanting to seek attention and jealousy marked by the freedom given to children to behave according to their own wishes.